HUBUNGAN KEBIASAAN SARAPAN PAGI DENGAN TINGKAT KONSENTRASI BELAJAR PADA ANAK - Tamsuri, Anas; Ajeng, Galih (Jurnal AKP, 2012)
Concentration means the condition of someone who can focus the mind to onething. The ability to concentrate will affect the speed in capturing the materials we need. A student who have good ability to concentrate will easier to capture the material he was supposed to absorb. The purpose of this study is to determine the relationship between the breakfast habits and the level of concentration, in learning of children.Research design in this study was analytic crossectional. The population is all students in grade IV, V, VI. Its population in SDN Sukosari II was 76 children. Samples are most students in grade IV, V, VI in SDN Sukosari II amount to 64 children by using simple random sampling technique. Collection data for breakfast habits and the concentration level for learning in of student use questionnaires, then analyzed using cross tabulations and the correlation test used Spearman correlations. Results of research is obtained the better of breakfast habits, the better the level of concentration in children learning. From the research results from 64 respondents, only 9 children (14.1%) in the habit of breakfast is good category. And of those 8 of  9 children came in good categories and one child came in qiite categories. And it is  proven, indicates that there is relation of  the breakfast habits with the level of concentration in children learn. It can be concluded that breakfast habits affect the concentration level in children study. So, get children to have breakfast before going to school is very important. Because breakfast can improve concentration childrens learning.